Investigation of the Plasma Nitrite Levels and Oxidant–Antioxidant Status in Obstructive Sleep Apnea Syndrome - BOZKURT, Hakan (Noro Psikiyatr Ars, 2015)
INTRODUCTION: Obstructive sleep apnea (OSA) is one of the most prevalent sleep disorders. In the present study, we assessed the nitrite level, which is an indirect indicator of nitric oxide (NO), total oxidant status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI), which may be associated with endotel dysfunction. We investigated the difference between the groups and the relationship among the severity of comorbid conditions. METHODS: This study was conducted in 39 OSA patients confirmed by polysomnography and 40 healthy subjects (controls). The OSA group consisted of 10 women and 29 men and the control group consisted of 20 women and 20 men. Polysomnographic revealed mild OSA in two, moderate in 7 and severe in 30 cases. We measured plasma TAS, TOS and nitrite levels from venous blood. The OSI value was obtained by dividing the TOS and TAS values. Values were compared with the control group and between patient groups. RESULTS: A high body mass index (BMI), cardiovasculer diseases (CVD) and the use of medication for co-morbid diseases were more prevalent in the OSA group (p=.001, p=.029 and p=.006, respectively). The median plasma TOS level and OSI in the obstructive sleep apnea syndrome (OUA) group were significantly higher than those in the control group (p=.001 and p=.001, respectively). The plasma median nitrite level and TAS did not show any significant difference between the OSA and the control groups. None of the parameters revealed a significant difference between severe and moderate OSA cases. CONCLUSION: Our findings in the present study revealed that the oxidant–antioxidant balance shifted toward the oxidant side in OSA cases; however, the NO level did not change. These findings together may point out that some molecules other than NO may have a role in the pathophysiology of endothelial dysfunction and also in the disturbed oxidant–antioxidant balance in OSA.